PRODUKTIVITAS PENGANGKUTAN BATUBARA DENGAN ALAT BERAT PADA TAMBANG PT. OKA LINTAS MUARA DI SAMBOJA KABUPATEN KUTAI KERTANEGARA - sadzaly, muhson (KURVA S JURNAL MAHASISWA, 2012)
ABSTRACTÂ Sub-Province of Kutai Kartanegara, owning Natural Resources potency ( Very big SDA) for example coal mine, forest, coconut of sawit petroleum and. Stone embers mineral having tired deposit Â± 523.784.709 Metric Ton there are various district that is Loa Janan, Loa Kulu, Tenggarong Defect, Estuary of Muntai, Marangkayu, Samboja, Anggana, Estuary Rhinoceros, Town Wake Up, Estuary of Wis, Estuary of Kaman, and Tabang ( On Duty Mining Of Sub-Province of Kutai Kartanegara, year 2012).In execution of Transportation of Stone Smolder Area Mining very needed usage of heavy equipment, so that execution of work earn as according to goals which have been determined, therefore usage of heavy equipment have to be planned well and is careful, so that precisely its use is, optimal its production and existence of equipments efficiency.As for factors which need diperhatkan in election of usage of heavy equipment shall be as follows : Location and work type to be executed 1) Function and heavy equipment type to be used, like to dig, to transporting, and menggusur 2) Energy and heavy equipment capacities 3) Method and way of heavy equipment operation.As for Heavy equipment which using research location in the form of : Bulldozer Komatsu D-85, Excavator Komatsu PC200 and of Dump Truck Toyota Dyna 130HT.Pursuant to breakdown of above, hence this Final Duty, writer will study about analysis calculation of heavy equipment production used for the execution of Transportation of Coal in coal-mine location.